Model predictive control–based robust-control strategy of distribution control for a grid-connected AC microgrid - Halivor, James Xorse (Frontiers in Smart Grids, 2023)
In recent years, the task of ensuring the reliable functioning of power systems has become increasingly challenging due to the expanding complexity of power system networks. The diminishing availability of fossil fuels has compelled the global community to rely more heavily on renewable energy sources such as solar systems, wind power, and hydroelectric power. Consequently, there is a growing need for AC micro-grids to provide an efficient power distribution strategy. The power system networks composed of micro-grids often encounter a high rate of failures, exceeding 80%, due to their vulnerability to unforeseen fluctuations in various distributed generation sources within a micro-grid. These fluctuations significantly undermine the operational efficiency of the micro-grid and pose detrimental effects on the distribution system. The micro-grid is comprised of many distributed generation units and local loads. The load in a micro-grid exhibits parametric uncertainty, which contributes to the variability observed in its performance. The control approach has been formulated with the objective of attaining resilient performance even when confronted with unaccounted-for loads, dynamic loads, harmonic loads, as well as balanced and unbalanced loads. The design is showcased by utilizing the outcomes to ensure the smooth operation of the distribution procedure in micro-grid power systems. In this study, the authors have designed a control method that is based on Model Predictive Control (MPC) and is both robust and optimal. Model Predictive Control (MPC) possesses the capability to anticipate the future behavior of a given system. By considering the healthy characteristics of power distribution, the controller is able to effectively address and minimize any disturbances that may arise within the system. The model is applied within the MATLAB Simulink environment, wherein it yields an ideal and suitable total harmonic distortion (THD) value. This value serves as an indicator of the performance quality of the controller and the enhanced efficiency of the micro-grid system.